Analysis of Creative Thinking Ability Judging from the Confidence of Class XI Students of SMA Negeri 1 Bambanglipuro - Wahyu Septina Anggraini; Vita Istihapsari (Phenomenon : Jurnal Pendidikan MIPA, 2021)
Abstract The purpose of this study was to describe the creative thinking ability of class XI students of SMA Negeri 1 Bambanglipuro in terms of high, medium and low levels of confidence in the material of sequences and series. This research is a descriptive qualitative research. The subjects of this study were 6 students of class XI IPS 1 at SMA Negeri 1 Bambanglipuro with high, medium and low levels of self-confidence. Data collection techniques used in this study were questionnaires, tests and interviews, then the data obtained were analyzed using data triangulation techniques. This study resulted that subjects with a high level of self-confidence at TKBK 4 (very creative) were able to meet all aspects of creative thinking indicators, namely, fluency, flexibility and novelty and being at TKBK 3 (creative) were able to meet the indicators of creative thinking, namely fluency and flexibility. Subjects with a moderate level of self-confidence at TKBK 3 (creative) were able to meet the creative thinking indicators, namely fluency and flexibility. Meanwhile, subjects with low self-confidence were at TKBK 2 (creative enough) were able to meet the flexibility creative thinking indicator and were at TKBK 1 (less creative) were able to meet the creative thinking indicator, namely fluency. Keywords: Creative Thinking Ability, Self Confidence, Lines and Series